Defining competencies in curriculum and instruction and developing a new competency model - Mehmet Kart; Hüseyin Şimşek (Humanities & Social Sciences Communications)
Abstract This research aims to define competencies and propose a new competency model based on expert opinions. Using the Delphi technique, a qualitative research approach was employed. Data were collected through three rounds of Delphi surveys from 29 experts at universities with doctoral programmes in the field of Curriculum and Instruction (CI), who hold doctoral degrees in this area. In the first round, open-ended questions enabled experts to identify key competencies for CI. The subsequent rounds refined these competencies into a 7-point Likert scale questionnaire. Content and descriptive analysis were applied to the first round, while measures of central tendency and dispersion analysed the second and third rounds. The study culminated in a model encompassing 22 competencies: 5 in knowledge, 10 in skills, and 7 in attitudes and values. The knowledge domain includes sub-competencies such as possessing and deepening knowledge. The skills domain covers areas like teamwork and leadership, knowledge dissemination, independent working, problem-solving, and critical thinking, along with innovative and analytical thinking. The attitudes and values domain comprises professional sensitivity, lifelong learning, and commitment to ethical principles and values. This competency model aligns with the European Qualifications Framework (EQF) and the National Qualifications Framework for Higher Education in Türkiye (NQF-HETR), offering a robust framework for CI doctoral programmes. This model not only enhances the quality of CI education but also ensures alignment with international standards.